Zika virus in the Americas: A New Global Health Emergency - Molina, Nora Beatriz (2016)
Нe World Health Organization (WHO) has warned of the rapid spread of Zika virus (ZIKV). In February 2016, Dr. Margaret Chan has declared the ZIKV and its suspected link to birth defects an public health emergency of international concern (PHEIC). ZIKV is a member of the flDvLvLrus family, which also includes Yellow fever virus, Dengue virus, Japanese encephalitis virus, and West Nile virus. Virions are spherical (40-50 nm in diameter) with a positive-sense, nonsegmented, single-stranded RNA genome (~10.8 Kb). НLs virus has two lineages (or genotypes) dLوٴerent, African and Asian lineages. Information regarding pathogenesis of ZIKV is scarce but mosquito-borne flDvLvLruses could replicate in dendritic cells near the site of inoculation and spread to lymph nodes and the bloodstream. To date, ZIKV RNA has been detected in blood, urine, semen, saliva, cerebrospinal fluLd, amniotic fluLd, and breast milk.